THE CONCEPT OF FEMINISM IN THE INTERIOR SPACE OF WOMEN SPECIAL FITNESS CENTERS - Cintya, Siti Rahmah; Fatimah, Dina (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2024)
The purpose of this research is to review the concept of feminist architecture in fitness facilities specifically for women. Women’s fitness or gyms facilities are becoming increasingly relevant in the era of health and fitness awareness, women’s gyms are facilities that provide fitness services that are tailored to the needs and preferences of women. The study reviewed the concept of feminism in women’s fitness facilities. The research methods used are qualitative methods with descriptive analysis approaches, with data collection techniques through observations, interviews, and literature studies. Therefore, through this research will be presented findings that show that women’s fitness facilities have some characteristics of feminism architecture, among others the clear distribution of space between private and public spaces, fine and unrigid architectural punches by playing curved fields, the use of colors and ornaments that depict the feministic nature of femininity, as well as the provision of facilities that support the comfort and safety of women